2018
DOI: 10.3164/jcbn.17-115
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease remission in men through regular exercise

Abstract: Recent cross-sectional and randomized controlled studies of small sample sizes revealed that regular exercise is effective for improving nonalcoholic fatty liver disease. However, there has been no large-scale longitudinal study addressing the effect of regular exercise on remission of nonalcoholic fatty liver disease. Thus, we investigated the impact of exercise on the natural history of nonalcoholic fatty liver disease. We analyzed 1,010 (860 men and 150 women) Japanese participants who received health check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
9
1
1
Order By: Relevance
“…There have been several longitudinal cohort studies on lifestyle habits involved in the development or remission of NAFLD. However, most of these studies assessed lifestyle habits at baseline but not changes in these habits during the study period 14,[16][17][18]26 . We conducted a longitudinal cohort study to investigate the association of the development or remission of NAFLD with favorable changes in the lifestyle habits during follow-up period: weight loss, starting to exercise, quitting smoking, and stopping eating dinner within 2 hours of going to bed.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several longitudinal cohort studies on lifestyle habits involved in the development or remission of NAFLD. However, most of these studies assessed lifestyle habits at baseline but not changes in these habits during the study period 14,[16][17][18]26 . We conducted a longitudinal cohort study to investigate the association of the development or remission of NAFLD with favorable changes in the lifestyle habits during follow-up period: weight loss, starting to exercise, quitting smoking, and stopping eating dinner within 2 hours of going to bed.…”
Section: Discussionmentioning
confidence: 99%
“…IR plays an important role in NAFLD by promoting free fatty acid storage [ 44 ], and this hyperinsulinemia activates the lipogenic factors of transcriptional regulators including fatty acid synthase and sterol regulatory element binding protein-1c (SREBP1c) [ 29 ]. Therefore, changes in the pathways of fatty acid synthesis and fatty acid oxidation play key roles, and exercise training may have a protective effect against fatty liver by activating the AMPK pathway and/or suppressing the SREBP1c pathway [ 45 ]. These results support previous studies and showed that there were remarkable improvements in IR, fasting blood glucose, and lipid profile in the training groups, which seemed to be major contributors to the relative improvement of the liver parenchyma in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…72 suggested that the pathogenesis involved in steatosis and cellular injury is thought to be related to insulin resistance and oxidative stress, so the management can be done by identifying and treating the metabolic risk factors, improving insulin sensitivity and increasing antioxidant defenses in the liver along with weight management and life style modification. A study had been conducted by Osaka T, et al, 2018. 73 to understand the benefit of exercise in NAFLD.…”
Section: G Study Reports Related To Treatment Of Nafldmentioning
confidence: 99%
“…A study had been conducted by Osaka T, et al, 2018. 73 to understand the benefit of exercise in NAFLD. They enrolled 1,010 individuals (860 men and 150 women) in their study.…”
Section: G Study Reports Related To Treatment Of Nafldmentioning
confidence: 99%